The Falkland Islands War: An Image of War in the 21st Century. - Allard, J. C. (1997)
The 1982 war in the Falkland Islands and surrounding waters in the South Atlantic Ocean marked dramatic changes in the contemporary world. By any reckoning, it was a war that should never have been fought. It was a war unlike any other war in the twentieth century, and since 1945 it was the first war to erupt outside the construct of the Cold War paradigm. The ten week war between Great Britain and Argentina clearly demonstrated the military and diplomatic power of the western democracies, and paved the way for the United States' incursions into Grenada, Panama, and even the Gulf War of 1990-91. This analysis will examine the Falklands conflict as a prototype of future wars.